Inhibition of inwardly rectifying Kir2.x channels by the novel anti-cancer agent gambogic acid depends on both pore block and PIP2 interference - Scherer, Daniel; Xynogalos, Panagiotis; Scholz, Eberhard P.; Thomas, Dierk; Katus, Hugo; Zitron, Edgar (Naunyn-Schmiedeberg's archives of pharmacology, 2017)
The caged xanthone gambogic acid (GA) is a novel anti-cancer agent which exhibits anti-proliferative, anti-inflammatory and cytotoxic effects in many types of cancer tissues. In a recent phase IIa study, GA exhibits a favourable safety profile. However, limited data are available concerning its interaction with cardiac ion channels. Heteromeric assembly of Kir2.x channels underlies the cardiac inwardly rectifying IK1 current which is responsible for the stabilization of the diastolic resting membrane potential. Inhibition of the cardiac IK1 current may lead to ventricular arrhythmia due to delayed afterdepolarizations. Compared to Kv2.1, hERG and Kir1.1, a slow, delayed inhibition of Kir2.1 channels by GA in a mammalian cell line was reported before but no data exist in literature concerning action of GA on homomeric Kir2.2 and Kir2.3 and heteromeric Kir2.x channels. Therefore, the aim of this study was to provide comparative data on the effect of GA on homomeric and heteromeric Kir2.x channels. Homomeric and heteromeric Kir2.x channels were heterologously expressed in Xenopus oocytes, and the two-microelectrode voltage-clamp technique was used to record Kir2.x currents. To investigate the mechanism of the channel inhibition by GA, alanine-mutated Kir2.x channels with modifications in the channels pore region or at phosphatidylinositol 4,5-bisphosphate (PIP2)-binding sites were employed. GA caused a slow inhibition of homomeric and heteromeric Kir2.x channels at low micromolar concentrations (with IC50 Kir2.1/2.2 < Kir2.2 < Kir2.2/2.3 < Kir2.3 < Kir2.1 < Kir2.1/2.3). The effect did not reach saturation within 60 min and was not reversible upon washout for 30 min. The inhibition showed no strong voltage dependence. We provide evidence for a combination of direct channel pore blockade and a PIP2-dependent mechanism as a molecular basis for the observed effect. We conclude that Kir2.x channel inhibition by GA may be relevant in patients with pre-existing cardiac disorders such as chronic heart failure or certain rhythm disorders and recommend a close cardiac monitoring for those patients when treated with GA.
Gesehen am 12.06.2018
Im Titel ist "2" in "PIP2" tiefgestellt
First online: 02 April 2017